2022
DOI: 10.1186/s12893-022-01472-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and treatment outcomes of occult breast cancer: a population-based study

Abstract: Background Occult breast cancer (OBC) is a special type of breast cancer. Because of its rarity, clinicopathological information is still insufficient, causing a controversial condition about its treatment recommendation. Thus, we aimed to clarify major clinicopathological information, treatment strategies and prognosis of OBC based on a large population. Methods We retrospectively collected adult female OBC population from Surveillance, Epidemiolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In the previous studies, among the subtypes of OBC, the luminal A subtype was the most common (27.40%) while HER-2 positive OBC merely accounted for about 6.20% ( 8 ). The subtypes of IHC of OBC showed no significant difference in prognosis.…”
Section: Discussionmentioning
confidence: 88%
“…In the previous studies, among the subtypes of OBC, the luminal A subtype was the most common (27.40%) while HER-2 positive OBC merely accounted for about 6.20% ( 8 ). The subtypes of IHC of OBC showed no significant difference in prognosis.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that local therapy provides a survival benefit for OBC patients (8,13,19,20); however, the benefit does not change significantly based on the type of local therapy. In contrast to our results, a retrospective study, which also used data from the SEER database, suggested that there was no difference in the prognosis of all N stage OBC patients who received radiotherapy and surgery (6).…”
Section: Discussionmentioning
confidence: 94%
“…Thus, combined ALND and adjuvant radiotherapy should be considered the primary treatment modality for such patients. A recent study based on the SEER database concluded that the type of surgery does not affect the prognosis of OBC patients and additional radiotherapy provides a survival benefit for OBC patients ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since this type of breast cancer is quite rare, its prognosis remains debatable, and standardized management of OBC is still difficult [1,6]. Some large-sample retrospective studies using SEER could help solve the problem of rare cases, but most such cases in previous studies have a large time span [7,20,21] and some cases that were not OBC might have been considered so in the past because of the limitations of imaging technology [6,32,33]. The present study, as far as we are aware, is the most up-to-date one to examine the clinical traits and prognosis of OBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been challenging to conduct randomized controlled trials and standardize management because this particular type of breast cancer is extremely rare. A lot of retrospective studies focus on the effect of different treatment methods on the prognosis of all OBC patients [7,[17][18][19][20][21], but no one has analyzed it in relation to different molecular subtypes, hence there is a need for a further inquiry.…”
Section: Introductionmentioning
confidence: 99%